Influence Self Monitoring Blood Glucose (SMBG) and Diabetes Self Management Education (DSME) on the Stability of Blood Glucose Levels - Susanti Susanti; Difran Nobel Bistara (Jurnal Keperawatan Respati Yogyakarta, 2023)
Diabetes Mellitus (DM) sufferers must do DM management behavior (self-management) to control their Blood glucose levels and prevent complications. To achieve optimal self-management behavior, one of the efforts made is SMBG and DSME. Self-Monitoring Blood Glucose (SMBG) is self-monitoring blood glucose using a glucometer. Diabetes Self-Management Education (DSME) is an ongoing process of facilitating the knowledge, skills, and abilities needed for diabetes self-care. This study contributes to analyzing the effect of Self-Monitoring Blood Glucose (SMBG) and Diabetes Self-Management Education (DSME) on the stability of Blood glucose levels. The research design used is quasi-experimental. The sample in this study amounted to 40 and was taken using the technique of simple random sampling. Stability of Blood glucose levels using a glucometer measuring instrument. Data analysis using test Wilcoxon Signed-rank. The results of statistical tests on SMBG showed a p-value (0.001), so it could be concluded that there was an effect of SMBG on the stability of Blood glucose levels. Statistical test results on DSME showed a p-value (0.000), so it can be concluded that there is an effect of DSME on the stability of Blood glucose levels. Adherence to structured SMBG allows sufferers to interpret results regarding their activity level and portion size. It motivates them to act on these results for better blood sugar results. DSME components taught to patients can increase patient knowledge and skills and improve patient care that is not correct.